Development of Blueberry-Derived Extracellular Nanovesicles for Immunomodulatory Therapy - Tuong Ngoc-Gia Nguyen; Cuong Viet Pham; Rocky Chowdhury; Shweta Patel; Satendra Kumar Jaysawal; Yingchun Hou; Huo Xu; Lee Jia; Andrew Duan; Phuong Ha-Lien Tran; Wei Duan (Pharmaceutics, 2023)
Over the past decade, there has been a significant expansion in the development of plant-derived extracellular nanovesicles (EVs) as an effective drug delivery system for precision therapy. However, the lack of effective methods for the isolation and characterization of plant EVs hampers progress in the field. To solve a challenge related to systemic separation and characterization in the plant-derived EV field, herein, we report the development of a simple 3D inner filter-based method that allows the extraction of apoplastic fluid (AF) from blueberry, facilitating EV isolation as well as effective downstream applications. Class I chitinase (PR-3) was found in blueberry-derived EVs (BENVs). As Class I chitinase is expressed in a wide range of plants, it could serve as a universal marker for plant-derived EVs. Significantly, the BENVs exhibit not only higher drug loading capacity than that reported for other EVs but also possess the ability to modulate the release of the proinflammatory cytokine IL-8 and total glutathione in response to oxidative stress. Therefore, the BENV is a promising edible multifunctional nano-bio-platform for future immunomodulatory therapies.